Response based design metocean conditions for a permanently moored FPSO during tropical cyclones: Estimation of greenwater risk. (August 2019) - Chen, L.; Taylor, P.H.; Draper, S.; Wolgamot, H.; Milne, I.A.; Whelan, J.R.
Highlights: Response based analysis is used to determine the design metocean conditions of an FPSO in terms of greenwater severity. A numerical tool is developed to compute the mean vessel heading, validated with full-scale measurements. Long-term extrapolation is performed to provide 1 in N-year extreme relative wave-vessel motions. Both the most probable maximum and maximum individual relative wave-vessel motion within a storm are described. The incident wave groups causing maximum relative wave-vessel motion in selected design metocean conditions are described. Abstract: Response based analysis (RBA) is used to establish the design metocean conditions (DMCs) of a generic weather-vaning FPSO off the North West Shelf (NWS) of Australia for determining greenwater severity. A vessel heading prediction tool, an essential component of the RBA analysis for weather-vaning vessels, is developed and evaluated by comparing with full-scale measurements from an operating FPSO. Locations at the bow, amidships and the stern of the vessel are found to be susceptible to greenwater risks and the vessel is often exposed to oblique waves during tropical cyclones. Long-term extrapolation is performed to estimate 1 in. N-year return relative wave-vessel motions represented by both the most probable maximum relative wave-vessel motion within a storm r mp, and the maximum individual relative wave-vessel motion r Max . It is observed that r Max ˜ (1.1–1.2) r mp . The use of r Max allows for the variability of the short term maxima per storm and also the fact that the peak in response might not come in the most severe sea-state. Given the focus on greenwater rather than wave severity, the slightly larger value of r Max at a given return period is used for assessment of greenwater risk. The sea-states that lead to r Max at a 1 in 100 year level are identified and subsequently used for characterising the wave groups causing maximum relative wave-vessel motion at various locations around the vessel. For a given location, the shapes of the wave time histories which give rise to extreme relative wave-vessel motions in a set of design metocean conditions are similar, indicating that a 'design wave', derived within the framework of linear wave theory, may be a useful approach to tackle highly nonlinear and complex greenwater overtopping problems.